2011
DOI: 10.1111/j.1471-4159.2010.07136.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic activity of interleukin-17 and tumor necrosis factor-α enhances oxidative stress-mediated oligodendrocyte apoptosis

Abstract: J. Neurochem. (2011) 116, 508–521. Abstract Th1 cytokine‐induced loss of oligodendrocytes (OLs) is associated with axonal loss in CNS demyelinating diseases such as multiple sclerosis (MS)that contributes to neurological disabilities in affected individuals. Recent studies indicated that, in addition to Th1‐phenotype cytokines including tumor necrosis factor (TNF)‐α, Th17 phenotype cytokine, interleukin (IL)‐17 also involved in the development of MS. In this study, we investigated the direct effect of IL‐17 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 68 publications
(127 reference statements)
4
77
1
Order By: Relevance
“…Indeed, TNF-a was demonstrated to cause degeneration of oligodendrocytes in the MS brain (4,24). Previous reports suggested that TNF-a inhibits survival and differentiation of OPCs in a model of spinal cord injury (SCI) (25), enhances oxidative stress-induced oligodendrocyte apoptosis (26), and mediates oligodendrocyte cell death through a TNFR1-dependent mechanism (27). Although our data support the previous work implicating TNF-a as a key cytokine that can dramatically influence oligodendrocyte biology (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…Indeed, TNF-a was demonstrated to cause degeneration of oligodendrocytes in the MS brain (4,24). Previous reports suggested that TNF-a inhibits survival and differentiation of OPCs in a model of spinal cord injury (SCI) (25), enhances oxidative stress-induced oligodendrocyte apoptosis (26), and mediates oligodendrocyte cell death through a TNFR1-dependent mechanism (27). Although our data support the previous work implicating TNF-a as a key cytokine that can dramatically influence oligodendrocyte biology (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…The formation of free radicals, excitotoxicity, astrogliosis and release of cytokines by activated microglia are important downstream mechanisms that can damage the developing oligodendrocyte after inflammation and/or HI [53,65,66]. In particular, TNF-α has been described to negatively influencing oligodendrocyte maturation and/or induce oligodendrocyte death [53,67,68,69]. Apparently, the changes induced by LPS alone are not sufficient to induce white or gray matter damage in our mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…The increased percentage of Th17 cells in tumor tissues is associated with cytokines and chemokines released from tumor microenvironments (14,23,(41)(42)(43)(44). This study shows for the first time that the EBV ϩ C666 cells co-cultured with CD4 Six cytokines were found in the culture medium of NPC tumor tissues, with MIF being found in the greatest amount.…”
Section: Discussionmentioning
confidence: 99%